Virtual reality exercises targeting spinal alignment: a systematic review and meta-analysis - Rajabi Reza; Khorramroo Fateme; Mousavi Seyed Hamed; Hernandez Manuel Enrique (Biomedical Human Kinetics)
Study aim: Poor posture is a widespread issue in today’s world, emphasizing the importance of spinal posture for balance, stability, and efficient movement. We aimed to systematically review the impact of virtual reality (VR) exercises on correcting spinal alignment in healthy individuals or those with spinal deformities.